2023
DOI: 10.1038/s41597-023-02386-7
|View full text |Cite
|
Sign up to set email alerts
|

An open presurgery MRI dataset of people with epilepsy and focal cortical dysplasia type II

Abstract: Automated detection of lesions using artificial intelligence creates new standards in medical imaging. For people with epilepsy, automated detection of focal cortical dysplasias (FCDs) is widely used because subtle FCDs often escape conventional neuroradiological diagnosis. Accurate recognition of FCDs, however, is of outstanding importance for affected people, as surgical resection of the dysplastic cortex is associated with a high chance of postsurgical seizure freedom. Here, we make publicly available a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…As we know, preoperative lesion detection is the key to the success of surgery, which is the major assignment of radiologists. Nevertheless, artificial intelligence is gradually revolutionizing this job [ 23 ]. Conventionally, for refractory epilepsy brain MRI, neuroradiologists inevitably miss subtle lesions which can be detected by neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, preoperative lesion detection is the key to the success of surgery, which is the major assignment of radiologists. Nevertheless, artificial intelligence is gradually revolutionizing this job [ 23 ]. Conventionally, for refractory epilepsy brain MRI, neuroradiologists inevitably miss subtle lesions which can be detected by neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…It is described in detail in a previous work (Walger et al 2024). Here, we only analyze a subset of 85 FCD cases, which are part of the "open presurgery MRI dataset of people with epilepsy and focal cortical dysplasia type II" made publicly available by Schuch and colleagues (Schuch et al 2023) IIb 34…”
Section: Fcd Cohortmentioning
confidence: 99%
“…We showed that human performance depends on the presence of FCDspeci c MRI features; it is especially in uenced by FLAIR hyperintensity and cortical thickening. 85 of the FCD cases were made publicly available in a different work (Schuch et al 2023). The public dataset includes the defaced T1 and FLAIR images, the ground-truth lesion masks and other clinical information.…”
Section: Introductionmentioning
confidence: 99%